Application of the Allen–Oxley iterative method of phase retrieval to series of images obtained by focus variation - Lobato, Iván (2008)
The application of the iterative method of phase retrieval to series of images obtained at different defocus values is described and discussed. It is shown that the iterative scheme is robust in the presence of discontinuities in the phase. The application of these methods to a set of experimental images taken using X-ray imaging is investigated. A computer program which can reproduce the simulations and analyse experimental image data is briefly discussed.